Programska oprema COBISS3/Katalogizacija - Levičar, Janja (Knjižnica, 2017)
Purpose: The purpose of this research was to evaluate the module COBISS3/Cataloguing from cataloguers' point of view. We wanted to find out whether cataloguers are satisfied with the cataloguing module. Its advantages/disadvantages and impact on quality of bibliographic records were examined. Also cataloguers' opinions about system changes and about planned novelties were explored. Methodology/approach: A combination of quantitative and qualitative research method was used. 133 cataloguers were surveyed via an online questionnaire, only cataloguers who possess the cataloguing licence and who have created the highest number of bibliographic records during the last three years are selected. Afterwards semi-structured interviews were conducted with 12 cataloguers. Results: The cataloguers were satisfied with the cataloguing module. A spelling checker and integrated e-manuals were considered the most important advantages. The increased use of a computer mouse was found to be disturbing. Professional training for the COBISS system is estimated rather high, however a need for additional training is observed. Procedures to acquire the cataloguing licence were rated only a little lower. In future we may expect records of higher quality as the module provides good working conditions for cataloguers. The quality of records depends also upon the modernization of cataloguing rules. Research limitation: A sample of cataloguers is selected irrespective of the library type. Originality/practical implications: A complex methodological approach, taking into account a broader system context was used. It is the first research on the COBISS3/Cataloguing module including suggestions for further improvements.
Keywords: katalogizacija; cataloguing; COBISS; COBISS.net; cataloguing module; modul za katalogizacijo; katalogizatorji; cataloguers; vrednotenje; evaluation